Insecticide straightjackets pests - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
American scientists have developed an insecticide that traps caterpillars inside the straight-jacket of their old skin. Within five days they die of desiccation and starvation. The synthetic compound interferes with the caterpillar's normal cycle...